PENGARUH RELIGIOSITY TERHADAP MINAT BOYCOTT YANG DIMEDIASI OLEH BRAND ATTITUDE PRODUK PRO ISRAEL AMDK MEREK AQUA DI BANDUNG RAYA - Nur, Nursafitri; Tania Adialita (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The purpose of this study was to examine the effect of religiosity on boycott intentions, mediated by brand attitude, using acase study of pro-Israel products, Aqua, brand of bottled water in Bandung Raya. The population for this study comprised consumers aged 18 years and older who consume or use Aqua bottled water and reside in the Bandung Raya. The sampling technique used was convenience sampling, involving 90 respondents. Primary data was collected through an online survey using a cross-sectional method. The study used various analytical techniques, including validation and reliability tests for instrument accuracy, description test classical assumption tests, multiple regression tests, and hypothesis testing, and the Sobel test, all conducted using the Statistical Package for the Social Sciences (SPSS) version 25 well as using the sobel calculator from Interactive Mediation Test. The findings indicate that religiosity negatively affecting brand attitude and brand attitude negatively affects boycott intention. Furthermore, brand attitude can play a mediating role between religiosity and boycott intentions toward pro-Israel bottled water (AMDK) products of the Aqua brand in Bandung Raya.